101k views
12 votes

3(4x+1)-4x+3=-18

User Evanb
by
6.4k points

2 Answers

5 votes
x = -3

Solution:

Distribute
(3)(4x)+(3)(1)+-4x+3 = -18
12x + 3+ -4x + 3 = -18

Combine
(12x+-4x) + (3+3) = -18
8x+6 = -18
8x+6 = -18

Subtract 6 from both sides
8x+6-6 = -18-6
8x = -24

Divide both sides by 8
8x/8 = -24/8

x = -3
User James Faulcon
by
5.0k points
5 votes

Explanation:

Given that:

3(4x + 1) - 4x + 3 = -18

Multiply the number outside of the brackets with numbers on LHS.

⇛12x + 3 - 4x + 3 = -18

Shift variables on LHS and constant on RHS, changing it's sign

⇛12x - 4x = - 18 - 3 - 3

Subtract the values on LHS and RHS.

⇛8x = - 18 - 6

⇛8x = -24

Shift the number 8 from LHS to RHS.

⇛x = -24/8

Write the fraction in lowest form by cancelling method.

Therefore x = {-(24÷2)/(8÷2)}

= -12/4

= -3

Please let me know if you have any other questions.

User Kniganapolke
by
5.6k points